Marine hydrocarbonoclastic bacteria as whole‐cell biosensors for n‐alkanes. Issue 4 (15th April 2015) - Sevilla, Emma; Yuste, Luis; Rojo, Fernando
Summary Whole‐cell biosensors offer potentially useful, cost‐effective systems for the in‐situ monitoring of seawater for hydrocarbons derived from accidental spills. The present work compares the performance of a biosensor system for the detection of alkanes in seawater, hosted in either Escherichia coli (commonly employed in whole‐cell biosensors but not optimized for alkane assimilation) or different marine bacteria specialized in assimilating alkanes. The sensor system was based on the Pseudomonas putida AlkS regulatory protein and the PalkB promoter fused to a gene encoding the green fluorescent protein. While the E. coli sensor provided the fastest response to pure alkanes (25‐fold induction after 2 h under the conditions used), a sensor based on Alcanivorax borkumensis was slower, requiring 3–4 h to reach similar induction values. However, the A. borkumensis sensor showed a fourfold lower detection threshold for octane (0.5 μM), and was also better at sensing the alkanes present in petrol. At petrol concentrations of 0.0125%, the A. borkumensis sensor rendered a sevenfold induction, while E. coli sensor showed no response. We discuss possible explanations to this behaviour in terms of the cellular adaptations to alkane uptake and the basal fluorescence produced by each bacterial strain, which was lowest for A. borkumensis.